Some determinants of opposite-sex friendships initiation and dissolution - Salkičević, Svjetlana (Array, 2014)
From the evolutionary perspective, friends help us solve the adaptive problems of reproduction, our own survival and survival of our offspring. Opposite-sex friendships (OSFs) provide individuals with a wider net of quality friends, potential mates and protectors, with sex differences originating in parental investment differences: in OSFs men pursue sexual access, while females seek physical protection and long-term mate potential. We have investigated the relationship of sex, gender roles, sociosexuality (SOI) and romantic involvement with the reasons for OSFs initiation and dissolution in a sample of 94 female and 90 male heterosexual students of the Zagreb University. OSF initiation because of sexual attraction and availability is more important to men and participants with higher SOI, while friendship dissolution for the same reason is more important to those with higher SOI, masculinity and femininity. OSF initiation because of physical protection is more important to women and participants with higher femininity, and dissolution for the same reason is more important to women ; OSF initiation because of the romantic relationship potential of a friendship is more important to men. These findings can be explained by sex differences in long-term mating strategies, rendering the reasons for the initiation of OSFs similar to those for engaging in a long-term romantic relationship.